Bilateral parotid gland metastases from carcinoma of the breast that presented 25 years after initial treatment. Issue 1 (January 2015) - Duncan, M.; Monteiro, M.; Quante, M.
Abstract We report a case of a 76-year-old woman with metastases to both parotid glands almost 25 years after mastectomy and chemotherapy for primary carcinoma of the breast. Immunohistochemical staining is invaluable in establishing the origin of metastatic deposits, in this case, expression of oestrogen receptors in a previously resected adenocarcinoma of the breast. The information can be used to target treatment accurately in selected cases of advanced malignancy.